The Effect Of Investment Knowledge And Investment Risk On Investment Interest In The Capital Market Among The Community Of Bengkulu Selatan Regency - Fadila, Ayu; Soleh , Ahmad; Harwini, Dewi (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
Investment is a way to boost the economy and welfare of a nation's people, including Indonesia. Someone who has invested means that they have prepared for their future and are ready to face emergencies.This research employs an explanatory research design with a quantitative approach. The population of this study consists of 370 households in Manna City, with a total sample of 78 respondents determined using the Slovin formula and the accidental sampling technique. Data were collected through observation, questionnaires, and literature study. The research instruments were tested using validity and reliability tests to ensure accuracy and consistency. Data analysis was carried out using SPSS version 25, including classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation tests), multiple linear regression analysis, t-test (partial), F-test (simultaneous), and the coefficient of determination (R²). The results indicate that: (1) Investment knowledge (X₁) has a positive and significant effect on investment interest among the community of Bengkulu Selatan Regency, with a t-count value of 3.719 > t-table value of 1.665 and a significance value of 0.000 < 0.05. (2) Investment risk (X₂) also has a positive and significant effect on investment interest, with a t-count value of 8.116 > t-table value of 1.665 and a significance value of 0.000 < 0.05. (3) Simultaneously, both independent variables have a significant effect on the dependent variable, with an F-count value of 331.108 > F-table value of 3.12 and a significance value of < 0.05. The coefficient of determination (R²) is 0.896, which means that investment knowledge and investment risk together contribute 89.6% to investment interest among the community.